Intersection of social behavior and legislative measures in reducing indoor tobacco smoke exposure in India - Mamta Verma; Arpita Basak; Bhupendra Kumar Verma; Mousumi Nath Mazumder; Vivek Verma (Clinical Epidemiology and Global Health, 2025)
Background: Indoor exposure to tobacco smoke in India is a significant social concern, primarily because it poses severe health risks not only to smokers but also to non-smokers who are exposed to secondhand smoke. The objective of the present study is to investigate the efficacy of current state and central tobacco as an intervention to control policies and laws in reducing indoor exposure to tobacco smoke and to assess the magnitude of such exposure in states implementing either only central regulations or integrated both state and central tobacco control measure. Method: ology: The study considered cross-sectional survey data of National Family and Health Survey (NFHS-4, 2015–16). Binary logistic regression with multiple covariates has shown an inclination of indoor smoking in states having single (Central) comparing with multiple (Central and State legislation) anti-smoking laws, particularly in rural areas, among economically weaker sections; among BPL households and within lower educational attainment populations, and also revealed influence of these factors in interaction with other. Results: Obtained results have shown that Indian States implemented only single anti-smoking laws reported significantly higher prevalence (31.0 %) i.e., twice of indoor exposure to tobacco smoke among children than States implemented multiple laws(15.4 %). The same inequality observed at every socio-demographical and economical levels such as based on residence(in rural[ORsingle-1.86(1.83–1.90); ORmultiple-1.75(1.72–1.79)]), caste levels(among tribe[ORsingle-1.80(1.77–1.83); ORmultiple-1.57(1.52–1.61)] except unreserved, economical status (among poorer [ORsingle-1.25(1.23–1.28); ORmultiple-1.23(1.20–1.27)]. Conclusion: Indoor tobacco smoke exposure is not just a public health concern but also a social issue, which requires urgent state and central tobacco control legislative reform and effective enforcement to safeguard the health and well-being of India's population.